Dynamics of Particle Formation by Electric Synchronous Explosion of Wires; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Zolnikov K. P.; Kryzhevich D. S.; Korchuganov A. V.; Psakhie S. G. Sergey Grigorievich (2015, 2015)
Title screen